(untitled) (Journal of Governance and Development (JGD), 2023)
Despite the widely recognised benefits of migration, there is currently a multiplicity of administrative challenges as well as high levels of poverty which limit the number of potential voluntary legal migrants in Africa. Against this background, the paper assesses the Southern African Development Community’s (SADC) migration governance regime and discusses how member states can enhance the development prospects of their respective countries if they work towards the reduction and elimination of restrictions to movement of their populations within the framework the African Continental Free Trade Area (AfCFTA). Qualitative methods are used in data collection and analysis. The paper relies on secondary sources of data such as published book chapters, journal articles and occasional reports. The data is analysed thematically. The findings reveal that despite the existence of AfCFTA, SADC and its member states have not utilised this initiative to encourage the free movement of goods and people and ultimately promote sustainable development in the region. The major regional economies such as South Africa, Botswana and Namibia are reluctant to promote free movement of people and goods in Africa and SADC. Despite having genuine concerns about migration, it is recommended that major regional economies should put regional interests ahead of national interests if the free movement of goods and people and sustainable development is to be achieved at both the continental and regional level.